ChemInform Abstract: Synthesis and Photophysical Properties of Tetra‐ and Pentaalkynylfluorobenzenes by Sonogashira Reactions of Novel Iodofluorobenzenes. Issue 25 (3rd June 2013) - Sharif, Muhammad; Maalik, Aneela; Reimann, Sebastian; Iqbal, Jamshed; Patonay, Tamas; Spannenberg, Anke; Villinger, Alexander; Langer, Peter
Abstract A series of 25 novel fluorescent tetra‐ and pentaalkynylfluorobenzenes is prepared.